A CACTA-like transposon in the Anthocyanidin synthase 1 (Ans-1) gene is responsible for apricot fruit colour in the raspberry (Rubus idaeus) cultivar 'Varnes'. - Daniel James Sargent; Matteo Buti; Stefan Martens; Claudio Pugliesi; Kjersti Aaby; Dag Røen; Chandra Bhan Yadav; Felicidad Fernández Fernández; Muath Alsheikh; Jahn Davik; R Jordan Price (PLoS ONE)
Cultivated raspberries (Rubus idaeus L.) most commonly bear small, red, highly aromatic fruits. Their colour is derived predominantly from anthocyanins, water soluble polyphenolic pigments, but as well as red forms, there exist cultivars that display yellow- and apricot-coloured fruits. In this investigation, we used a multi-omics approach to elucidate the genetic basis of the apricot fruit colour in raspberry. Using metabolomics, we quantified anthocyanins in red and apricot raspberry fruits and demonstrated that, in contrast to red-fruited raspberries, fruits of the apricot cultivar 'Varnes' contain low concentrations of only a small number of anthocyanin compounds. By performing RNASeq, we revealed differential expression patterns in the apricot-fruited 'Varnes' for genes in the anthocyanin biosynthesis pathway and following whole genome sequencing using long-read Oxford Nanopore Technologies sequencing, we identified a CACTA-like transposable element (TE) in the second exon of the Anthocyanidin synthase (Ans) gene that caused a truncated predicted ANS protein. PCR confirmed the presence in heterozygous form of the transposon in an unrelated, red-fruited cultivar 'Veten', indicating apricot fruit colour is recessive to red and that it may be widespread in raspberry germplasm, potentially explaining why apricot forms appear at regular intervals in modern raspberry breeding populations.